How To Build a Digital Librarian - an American-European Curricula Comparison Study - Vrana, Radovan (Array, 2002)
This paper covers two topics. The first topic is dedicated to the identification of necessity of human assistance in digital libraries i.e. the need for presence of librarians as mediators between users and paper and digital resources. This part of the paper consists of literature review, which will serve as a basis for the second topic. The second topic consists of a small-scale curricula comparison study. This part is limited to a selection of the American and the British universities, which are clearly identified on the Internet as library schools. Finally, the aim of this paper is to present a few basic ideas about some of the current trends in education of future librarians by comparing university curricula. The results should help students in choosing courses and educators in considering changes in their university curricula.